The SSCI Syndrome in Taiwan’s Academia - Chou, Chuing Prudence (Education Policy Analysis Archives, 2014)
With the global expansion of higher education in the last two decades, the maintenance of academic quality to meet requirements for international competitiveness has become a critical issue for policymakers and universities. In addition, the neoliberal emphasis on the market has increased the competition for global university rankings, and this emphasis continues to have consequences for university autonomy and academic governance. To cope with these challenges, Taiwan has introduced strategies for benchmarking its leading universities. Under the new evaluation system, universities are evaluated by external standards instead of those ensuring academic autonomy or contributions to society. This article details how these recent policy reforms have given rise to a new ‘SSCI syndrome’, which risks turning faculty members into paper producers rather than public intellectuals. These changes have also impacted students’ rights as well as the greater goals of academic development. The article then argues that, as voices from both within and outside of Taiwan’s academia have begun to respond to the issue, it begs the question as to whether or not Taiwan can serve as a model for the many other non-English-speaking countries of the academic ‘periphery’ who are currently confronting similar issues. Given the increasing global pervasiveness of this SSCI syndrome, understanding the effects of policies recently implemented in Taiwan has important implications for higher education throughout the world.